Left-sided malignant pleural mesothelioma presenting with recurrent pneumothorax 7 years after the right pleuropneumonectomy - Aydoğmuş, Ümit; Ugurlu, Erhan; Turk, Figen; Yuncu, Gokhan (The European Research Journal, 2016)
Malignant pleural mesothelioma (MPM) is an extremely aggressive tumor arising from the pleura with a median survival of approximately 9–12 months. It can rarely present as a spontaneous pneumothorax. We herein reported a 65-year-old female patient with the left-sided MPM presenting with episodes of recurrent spontaneous pneumothorax. She had undergone the right pleuropneumonectomy due to the right-side MPM 7 years ago. She admitted to our clinic with diagnosis of left pleural effusion. The patient underwent pleural biopsy and talc pleurodesis by thoracoscopy. Histologic study showed the epithelial subtype of MPM. She received chemotherapy nine times. Seven years after the right pleuropneumonectomy, she had recurrent left-sided spontaneous pneumothorax four times that was treated one by one with tube thoracostomy. We did not perform surgical treatment because of the unsuitable status of the patient. It should be kept in mind that, when pneumothorax develops in the remaining lung after a single-sided pneumonectomy, this may be due to the tumor.